Exploring the mechanism of action of aspirin in improving endometrial receptivity in PCOS rats based on uterine lavage fluid metabolomics - Ying Zhang; Xi Wang; Yiqing He; Quan Liu; Shuo Yang (PLoS ONE, 2025)
Backgrounds Aspirin has been shown to enhance endometrial receptivity (ER) during the window of implantation in patients with polycystic ovary syndrome (PCOS). However, the underlying mechanisms remain unclear. This study aimed to elucidate the mechanisms by which aspirin improves ER through metabolic analysis of uterine lavage fluid. Methods A PCOS rat model was established using letrozole. Body weight and estrous cycles were monitored, and the number of implanted embryos was assessed across groups. We evaluated endometrial ultrastructure, ovarian and endometrial histomorphometry. Serum levels of estradiol(E2) and progesterone(P)were measured. Moreover, through ultra-performance liquid chromatography-mass spectrometry, the study of uterine lavage fluid metabolites revealed the potential mechanism of action of aspirin. Results Compared with the model group, aspirin treatment significantly increased embryo implantation rates, improved endometrial morphology and hormone levels. Metabolomic analysis identified 48 differential metabolites, among which five—2, 6-dihydroxypurine, gluconolactone, Oxaceprol, PC (18:1/18:1), and PC (20:3e/17:1)—were identified as potential biomarkers for aspirin-mediated improvement of ER in PCOS rats. Pathway analysis revealed that aspirin primarily modulates the pentose phosphate pathway, arginine and proline metabolism, and glycerophospholipid metabolism. Conclusions Aspirin may enhance glucose metabolism, alleviate insulin resistance, promote angiogenesis, and improve vascular permeability and endometrial receptivity. These effects are likely mediated through the regulation of biomarkers involved in the pentose phosphate pathway, arginine and proline metabolism, and glycerophospholipid pathways in uterine lavage fluid.